Representations about sexuality of people diagnosed late with HIV infection - Luana Carla Santana Ribeiro; Maria Imaculada de Fátima Freitas; Mirian Santos Paiva
ABSTRACT Objective: to understand the representations about sexuality of people diagnosed late with HIV infection and its implications in the delayed search for diagnosis. Methods: this is a qualitative study, whose theoretical and methodological framework was Social Representation Theory. The research was carried out with 18 people diagnosed late with HIV infection through an open interview. For data analysis, Structural Narration Analysis was used, with support from MAXQDA 12®. Results: representations about sexuality contributed to delayed diagnosis, such as trust in a fixed partnership, sexual intercourse is natural, sexuality as a taboo, search for pleasure in sexual intercourse, regardless of risks, denial of risk for HIV infection. Final considerations: representations about sexuality participate in a web of stereotypes and riskier ways of living, which contribute to delayed diagnosis. Sexual health education remains necessary and essential throughout people's lives.